A hydroalcoholic extract of Senecio nutans SCh. Bip (Asteraceae); its effects on cardiac function and chemical characterization. (10th January 2023) - Palacios, Javier; Paredes, Adrián; Cifuentes, Fredi; Catalán, Marcelo A.; García-Villalón, Angel Luis; Borquez, Jorge; Simirgiotis, Mario J.; Jones, Matthew; Foster, Amy; Greensmith, David J.
Abstract: Ethnopharmacology relevance: The plant Senecio nutans SCh. Bip. is used by Andean communities to treat altitude sickness. Recent evidence suggests it may produce vasodilation and negative cardiac inotropy, though the cellular mechanisms have not been elucidated. Purpose: To determinate the mechanisms action of S. nutans on cardiovascular function in normotensive animals. Methods: The effect of the extract on rat blood pressure was measured with a transducer in the carotid artery and intraventricular pressure by a Langendorff system. The effects on sheep ventricular intracellular calcium handling and contractility were evaluated using photometry. Ultra-high-performance liquid-chromatography with diode array detection coupled with heated electrospray-ionization quadrupole-orbitrap mass spectrometric detection (UHPLC-DAD-ESI-Q-OT-MSn) was used for extract chemical characterization. Results: In normotensive rats, S. nutans (10 mg/kg) reduced mean arterial pressure (MAP) by 40% (p < 0.05), causing a dose-dependent coronary artery dilation and decreased left ventricular pressure. In isolated cells, S. nutans extract (1 μg/ml) rapidly reduced the [Ca 2+ ]i transient amplitude and sarcomere shorting by 40 and 49% (p < 0.001), respectively. The amplitude of the caffeine evoked [Ca 2+ ]i transient was reduced by 24% (p < 0.001), indicating reduced sarcoplasmic reticulum (SR) Ca 2+ content. Sodium-calcium exchanger (NCX) activity increased by 17% (p < 0.05), while sarcoendoplasmic reticulum Ca 2+ -ATPase (SERCA) activity was decreased by 21% (p < 0.05). LC-MS results showed the presence of vitamin C, malic acid, and several antioxidant phenolic acids reported for the first time. Dihydroeuparin and 4-hydroxy-3-(3-methylbut-2-enyl) acetophenone were abundant in the extract. Conclusion: In normotensive animals, S. nutans partially reduces MAP by decreasing heart rate and cardiac contractility. This negative inotropy is accounted for by decreased SERCA activity and increased NCX activity which reduces SR Ca 2+ content. These results highlight the plant's potential as a source of novel cardio-active phytopharmaceuticals or nutraceuticals. Graphical abstract: Image 1 Highlights: This study showed the hypotensive properties of the hydroalcoholic extract of S. nutans are associated with [Ca 2+ ]i handling and contractility in cardiac myocytes. The reduction of mean arterial pressure (MAP) by S. nutans was partly a result of decreased heart rate (HR) and ventricular contractility. Negative inotropy; decreased Ca 2+ -ATPase (SERCA) activity and increased Sodium-calcium exchanger (NCX) activity, reducing Ca 2+ content. Mass spectrometric detection showed the presence of the acetophenones dihydroeuparin and 4-hydroxy-3-(3-methylbut-2-enyl) acetophenone.